How effective are adaptation practices on offsetting sorghum and millet yield reductions under climate change? A Protocol for a Systematic Map - Akponikpe, P.B.I.; Allakonon, M.G.B.; Zakari, Sissou; Orou, B.Z.S. (CGIAR, 2024)
Sorghum and millet are essential staple crops used to improve food security and economic stability of semi-arid regions. However, increased recent threats and impacts due to climate change, raise concerns on how to maintain and even increase the yields of these two crops under the current evolving climate, especially in the short and the long terms. As solutions, several agronomic adaptation practices are promoted to limit the impacts of climate change on sorghum and millet yields. These practices range from conservation tillage, optimized planting dates, to drought-resistant crop varieties and water-saving irrigation. Nonetheless, while the benefits of adaptation practices on offsetting yield reduction caused by climate change in cereal crops such as maize, rice and wheat, are well known through systematic reviews, this knowledge remain limited for sorghum and millet crops. This proposal sets to investigate the current knowledge of the effectiveness of adaptation practices in offsetting yield reduction of sorghum and millet under climate change conditions using a systematic meta-analysis method. The result will help to inform on the best practices according to regions and crops for sustainable management for future food security and development.